Antibacterial Property of Hydroxyapatite with Ag+ Dopant Produced by Hydrothermal Process - Chen*, Hua-Jun; Wan, Lin (Asian Journal of Chemistry, 2013)
The antimicrobial powders of hydroxyapatite with Ag+ dopant were one-step synthesized with Ca(NO3)2·4H2O and AgNO3, (NH4)2HPO4 by hydrothermal method. It can be found that the concentration of Ag+ ions in hydroxyapatite powder has good linear relationship with the dosage of AgNO3. The analyses of XRD patterns show that the Ag-hydroxyapatite powder has the same crystal structure and functional group with hydroxyapatite powder, which indicates that the Ag-hydroxyapatite powder exhibits the structural properties of pure hydroxyapatite powder. Through calculations of EDS and XRF, it is known that the Ca2+ ions in crystal structure of hydroxyapatite powder can be substituted partially by Ag+ ions in hydrothermal condition, which synthesize the final product AgxCa10-x(PO4)6(OH)2. The result of antibacterial experiment shows that the produced Ag-hydroxyapatite powder has good antibacterial property, the MIC £ 50 μg/mL (Escherichia coli and Staphylococcus aureus).